2014
DOI: 10.1371/journal.pone.0084880
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Induced Conformational Changes in Genomic DNA from Cancerous K562 Cells Influence Drug-DNA Binding Modes

Abstract: Normal human genomic DNA (N-DNA) and mutated DNA (M-DNA) from K562 leukemic cells show different thermodynamic properties and binding affinities on interaction with anticancer drugs; adriamycin (ADR) and daunomycin (DNM). Isothermal calorimetric thermograms representing titration of ADR/DNM with N-DNA and M-DNA on analysis best fitted with sequential model of four and three events respectively. From Raman spectroscopy it has been identified that M-DNA is partially transformed to A form owing to mutations and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…It should be noted that, PLSR over the high concentration range, up to 50 μM, (Figure A) results in a spectral profile which is similar to those of DOX and ACT (Figure ) exhibiting strong features at 785 cm −1 (DNA backbone O─P─O) and 813 cm −1 (RNA O─P─O phosphodiester band stretching), while regression over the lower concentration up to the IC 50 of 1.2 ± 0.2 μM showed a decrease in features at 728, 830 and 1425 cm −1 , related to DNA B form and an increase in features at 668 and 675 cm −1 , related to DNA A form, indicative of conformational changes due to partial transition of the DNA B form to DNA A form due to Cisp binding .…”
Section: Raman Microspectroscopy For Chemotherapeutic Pre‐clinical Scmentioning
confidence: 58%
“…It should be noted that, PLSR over the high concentration range, up to 50 μM, (Figure A) results in a spectral profile which is similar to those of DOX and ACT (Figure ) exhibiting strong features at 785 cm −1 (DNA backbone O─P─O) and 813 cm −1 (RNA O─P─O phosphodiester band stretching), while regression over the lower concentration up to the IC 50 of 1.2 ± 0.2 μM showed a decrease in features at 728, 830 and 1425 cm −1 , related to DNA B form and an increase in features at 668 and 675 cm −1 , related to DNA A form, indicative of conformational changes due to partial transition of the DNA B form to DNA A form due to Cisp binding .…”
Section: Raman Microspectroscopy For Chemotherapeutic Pre‐clinical Scmentioning
confidence: 58%
“…When a cell enters apoptosis, the DNA shifts to a more disordered state, and the DNA signal in an infrared spectrum typically decreases 46 . A shift in the DNA band can also be observed in cells which have been treated with a drug known to intercalate with DNA, whose mode of action is such that base pairing is interrupted and unravelling from orderly B-DNA to the more disordered A-DNA form occurs 47 .…”
Section: Resultsmentioning
confidence: 99%
“…They showed the interaction between anticancer drugs (adriamycin and daunomycin) and DNA. The Raman results indicated that the mutated DNA remained partially transformed to the A-DNA form, owing to mutations, while the genomic DNA changed its conformation upon the interaction with the drug [47]. Wood et al studied the interaction between few platinum drugs and DNA.…”
Section: Dna Lesions Studied By Spectroscopic Methodsmentioning
confidence: 99%